Impact of legislation on registration of acutely toxic pesticides in Brazil - Garcia Garcia, Eduardo (2005)
OBJECTIVE: To evaluate the impact of the application of the "Pesticides Law" (Law no. 7,802/89) on the toxicological classification profile of registered pesticides in Brazil, from 1990 to 2000. METHODS: Data on registered commercial products in the years 1990 and 2000 were analyzed according to toxicological class, date of registration of the active ingredient (before or after the Law) and usage class (insecticides, fungicides, herbicides and others). Relative Identified Distribution Analysis was utilized for verifying statistical differences between distributions according to toxicological classes. RESULTS: Among the 863 registered commercial products in 2000, 46.6% were already registered before the Pesticide Law. Among the 461 commercial products registered after the Law, 59.2% were derivatives of active ingredients registered before the Law, and 41.4% were classified as highly hazardous (classes I and II of the Brazilian toxicological classification). No significant differences in toxicological classification profile were identified between the group of pesticides derived from active ingredients registered before the Law and the group derived from active ingredients registered after the Law (p